Technology-Based Islamic Religious Education: Literature Analysis of Trends, Challenges, and Opportunities - Sofyan Habibi Anhar; Puspo Nugroho (Badan Penerbit STIEPARI Press, 2025)
This study focuses on exploring technology-based Islamic religious education (PAI) and analyzing the literature related to trends, challenges, and opportunities for technology integration in PAI learning. The aim is to identify and analyze the literature related to technology implementation in PAI and provide recommendations for development. A systematic literature review method was used to analyze 15 articles published between 2020 and 2025. The results show that technologies such as mobile applications and e-learning platforms have great potential to improve the effectiveness of PAI learning; however, significant challenges remain, including limited infrastructure and lack of educator training. This literature synthesis highlights the importance of collaboration between educators, technology developers, and educational institutions to overcome these barriers. In conclusion, integrating technology into PAI learning can significantly improve the quality of education, but a number of challenges need to be considered to ensure effective and sustainable implementation.